Polycyclic aromatic azomethine ylides: A unique entry to extended polycyclic heteroaromatics - Berger, Reinhard; Wagner, Manfred; Feng, Xinliang; Muellen, Klaus (Chemical Science, 2015)
Based on polycyclic aromatic azomethine ylides (PAMYs), a metal-free "cycloaddition-planarization-sequence" is proposed, providing a unique entry to extended nitrogen-containing polycyclic aromatic hydrocarbons (N-PAHs). This method is highly versatile, as the structure of unprecedented N-PAHs can be tailored by the dipolarophile in the crucial 1,3-cycloaddition-reaction. Linear, as well as five- and six-membered cyclic dipolarophiles are successfully used. The geometric and optoelectronic nature of N-PAHs are investigated by UV-vis absorption and single crystal structure analysis. Remarkably, the newly synthesized N-PAHs demonstrate varying absorption profiles, covering the whole visible light range with rich photophysical properties, for example, fluorescent quantum yields up to 54%. This journal is
CRIS-Team Scopus Importer:2023-03-20